The translation of present perfect verb phrases in Sir Arthur Conan Doyle's the hound of the baskervilles into anjing setan - Yeli Setyawati (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2015)
ir.1/ws.c.1